C-V2X city-scale demonstration application - Wei LIU; Yipeng ZHANG; Xuying GUAN; Shangchao KUANG; Feng LI (Dianxin kexue)
China Mobile Communication Group Co.,Ltd.and industry parties have created the world’s first C-V2X city-scale demonstration application in Wuxi.The overall situation,goals and end-to-end technical solution of the project were introduced,including the overall system architecture,platform technical solution,V2X communication network technical solution,roadside system and terminal technical solution.At the same time,the project’s achievements in demonstration effects,technical verification,and industrial advancement were summarized,and the next plan for the project was proposed.The purpose was to provide reference for the development of other domestic demonstration areas,and to promote the rapid development of the internet of vehicles industry.